Being an Oleh in a Global World: From Local Ethnic Community to Transnational Community - Anteby-Yemini, Lisa (Hagar: Studies in Society and Culture, 2003)
The following article looks at two immigrant groups in Israel and suggests new approaches to the study of olim, or Jewish returnees to Israel, endeavoring to see them as migrants, similar to other countries in the world, with features such as transnationalism and globalization.